Signal Processing of Ultrasonic Data by Frequency Domain Deconvolution - ALI, Mohamed Galal Sayed; ELSAYED, Nour Zaky; EBEID, Mohamed Rafat (Walailak Journal of Science and Technology (WJST), 2013)
Digital deconvolution of ultrasonic echo signals improves resolution and quality of ultrasonic images. The signal is modeled as resulting from convolution of the Ultrasonic pulse with the reflectivity function with additive noise. A deconvolution in the frequency domain is used to estimate the reflectivity function. An approach to minimize the effects of the transducer is developed. The simulation of pulse echo operating into a medium of interest is deconvolved with the simulation of pulse echo transducers with different values of dynamic range. The technique has been successfully employed to an ultrasonic data model for reconstruction of reflectivity function and the final result shows an improved signal to nose ratio with better axial resolution.